6(5-2g)-3(-p+7)=

Simple and best practice solution for 6(5-2g)-3(-p+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(5-2g)-3(-p+7)= equation:


Simplifying
6(5 + -2g) + -3(-1p + 7) = 0
(5 * 6 + -2g * 6) + -3(-1p + 7) = 0
(30 + -12g) + -3(-1p + 7) = 0

Reorder the terms:
30 + -12g + -3(7 + -1p) = 0
30 + -12g + (7 * -3 + -1p * -3) = 0
30 + -12g + (-21 + 3p) = 0

Reorder the terms:
30 + -21 + -12g + 3p = 0

Combine like terms: 30 + -21 = 9
9 + -12g + 3p = 0

Solving
9 + -12g + 3p = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -12g + -9 + 3p = 0 + -9

Reorder the terms:
9 + -9 + -12g + 3p = 0 + -9

Combine like terms: 9 + -9 = 0
0 + -12g + 3p = 0 + -9
-12g + 3p = 0 + -9

Combine like terms: 0 + -9 = -9
-12g + 3p = -9

Add '-3p' to each side of the equation.
-12g + 3p + -3p = -9 + -3p

Combine like terms: 3p + -3p = 0
-12g + 0 = -9 + -3p
-12g = -9 + -3p

Divide each side by '-12'.
g = 0.75 + 0.25p

Simplifying
g = 0.75 + 0.25p

See similar equations:

| 6(2x+9)=(6x+12) | | 4v^2+24v+27=0 | | -44-6x=-x+16 | | H=-5t^2+80 | | -7x-8y=-20 | | y+8-3x-4=x-4x+2 | | 61+x=70 | | 7x-10.2=3.8 | | -30+7x=10+9x | | 0=2x^4-15x^2+7 | | 18b^4-39b^3+20b^2=0 | | 15-x=2x-3 | | 8x-154-3x=237+3x | | -5(r+8)=-92 | | 4(-4+k)+8(6+3j)= | | 7x+3y=73 | | 6log(4x-3)=18 | | 74+6x=-31+x | | x+0.07x+0.15(x+0.07x)=39 | | y+(y+17)=111 | | 8x-154-3=237+3x | | 6log(4x-1)=18 | | 4x=49-6x | | (2w+5)w=63 | | -3r=1(24-3r) | | 4t+6t^2-16=0 | | -4p-8=3p+36 | | 13=-5+2x | | x(t-x)-y*z=1 | | 4.1=5.3-0.2x | | (2w+1)w=66 | | x+y=420 |

Equations solver categories